The Effect of Energy Conservation Management on Fatigue in Patients with Chronic Kidney Disease Undergoing Hemodialysis: A Quasi-Experimental Study - Mailani, Fitri; Cahyati, Mia; Zulfiqar, Yevri; Huriani, Emil (Fakultas Ilmu-ilmu Kesehatan, 2026)
Fatigue is the most common complaint among patients with chronic kidney disease (CKD) undergoing hemodialysis. Energy conservation management involves modifying daily activities to reduce energy expenditure and alleviate fatigue. This study examines the impact of energy conservation management on fatigue levels in patients undergoing hemodialysis. This quasi-experimental study involved 52 hemodialysis patients who were randomly assigned to either the intervention or control group. The study was conducted in a hemodialysis unit at a public hospital in West Sumatra, Indonesia, from July to September 2024. The intervention group received energy conservation management training over a six-week period, comprising 12 sessions. Fatigue levels were assessed using the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) questionnaire. Data analysis was performed using paired and independent t-tests. The results showed a significant reduction in fatigue in the intervention group (p < 0.001). The mean (SD) fatigue score decreased from 28.92 (6.14) at baseline to 22.04 (4.41) after the 12 intervention sessions. Furthermore, a statistically significant difference in fatigue scores was observed between the intervention and control groups (p < 0.001). Effective energy conservation management reduces fatigue in hemodialysis patients. Nurses can teach this strategy to help patients manage fatigue in daily life